Expression of 11β-hydroxysteroid dehydrogenase type 2 is deregulated in colon carcinoma - Moravec, Martin; Svec, Jirí; Ergang, Peter; Mandys, Václav; Reháková, Lenka; Zádorová, Zdena; Hajer, Jan; Kment, Milan; Pácha, Jirí (Histology and histopathology, 2014)
Although the effects of glucocorticoids on proliferation, differentiation and apoptosis are well known, and steroid hormones have been identified to play a role in pathogenesis and the development of various cancers, limited data are available regarding the relationship between the local metabolism of glucocorticoids and colorectal adenocarcinoma (CRC) formation. Glucocorticoid metabolism is determined by 11β-hydroxysteroid dehydrogenases type 1 and 2 (11HSD1, 11HSD2), which increase the local concentration of cortisol due to the reduction of cortisone, or decrease this concentration due to the oxidation of cortisol. The objective of this study was to evaluate the extent of 11HSD1 and 11HSD2 mRNA in pre-malignant colorectal polyps and in CRC. The specimens were retrieved from patients by endoscopic or surgical resection and the expression of 11HSD1 and 11HSD2 was measured by real-time PCR. The polyps were of the following histological types: hyperplastic polyps and adenomas with low- or high-grade dysplasia. The neoplastic tissue of CRC obtained during tumor surgery was also studied. It was found that 11HSD2 was not only downregulated in CRC but already in the early stages of neoplastic transformation (adenoma with low-grade dysplasia). In contrast, the level of 11HSD1 was significantly increased in CRC but not in pre-malignant polyps. The results demonstrate that the downregulation of 11HSD2 gene expression is a typical feature of the development of colorectal polypous lesions and their transformation into CRC.
Keywords: Adenocarcinoma; prekancerózy; Humans; adenomové polypy; lidé středního věku; dítě; Down-Regulation; Biomarkers, Tumor; Child; Female; Aged; 11-beta-hydroxysteroiddehydrogenasa typ 1; dospělí; polymerázová řetězová reakce s reverzní transkripcí; mladý dospělý; Laser Capture Microdissection; senioři; lidé; 11-beta-Hydroxysteroid Dehydrogenase Type 2; Reverse Transcriptase Polymerase Chain Reaction; Adenomatous Polyps; down regulace; nádorové biomarkery; Adult; 11-beta-Hydroxysteroid Dehydrogenase Type 1; ženské pohlaví; Precancerous Conditions; kolorektální nádory; 11-beta-hydroxysteroiddehydrogenasa typ 2; Male; Middle Aged; Adolescent; transkriptom; Aged, 80 and over; laserová záchytná mikrodisekce; Real-Time Polymerase Chain Reaction; Transcriptome; Young Adult; senioři nad 80 let; adenokarcinom; mužské pohlaví; kvantitativní polymerázová řetězová reakce; Colorectal Neoplasms; mladiství